2018
DOI: 10.1007/s00204-018-2197-9
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter 2.5 damages skin cells by inducing oxidative stress, subcellular organelle dysfunction, and apoptosis

Abstract: The skin is the largest organ of the human body and the one mostly exposed to outdoor contaminants. To evaluate the biological mechanisms underlying skin damage caused by fine particulate matter (PM2.5), we analyzed the effects of PM2.5 on cultured human keratinocytes and the skin of experimental animals. PM2.5 was applied to human HaCaT keratinocytes at 50 µg/mL for 24 h and to mouse skin at 100 µg/mL for 7 days. The results indicate that PM2.5 induced oxidative stress by generating reactive oxygen species bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
204
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(223 citation statements)
references
References 57 publications
5
204
0
1
Order By: Relevance
“…PM 2.5 induces oxidative stress by generating reactive oxygen species (ROS), which leads to DNA damage and lipid peroxidation . Oxidative stress is a crucial mechanism of toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 induces oxidative stress by generating reactive oxygen species (ROS), which leads to DNA damage and lipid peroxidation . Oxidative stress is a crucial mechanism of toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Skin is the largest organ of the human body, as well as the primary organ which is exposed to outdoor contaminants. Exposure to PM causes epithelium damage, and endothelial dysfunction has been reported previously [8,9,38]. PM induce skin damages or diseases mainly through stimulating inflammatory response and oxidative stress [5,39].…”
Section: Discussionmentioning
confidence: 81%
“…The results indicated that PM significantly stimulated the expression of pro-inflammatory cytokines through activating NF-κB pathway [39]. Piao et al evaluated the effect of PM on human keratinocytes, and the results indicated that PM significantly induced oxidative stress by production of ROS, which causes lipid peroxidation, DNA damage, and protein carbonylation [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the depolarization of the mitochondrial membrane has become the basic method for detecting the early stage of cell apoptosis . The membrane‐permeant dye JC‐1 is widely used in apoptosis studies to monitor the status of mitochondria where JC‐1 accumulates in a potential‐dependent manner as indicated by a fluorescence emission shift from green ( ca 529 nm) to red ( ca 590 nm).…”
Section: Resultsmentioning
confidence: 99%